2009
DOI: 10.1007/s10554-009-9464-z
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve area: meta-analysis of diagnostic performance of multi-detector computed tomography for aortic valve area measurements as compared to transthoracic echocardiography

Abstract: Degenerative aortic valve stenosis (AS) has an incidence of 2-7% in the Western European and North American populations over 65 years of age. The aim of this study was to perform a meta-analysis of the published literature evaluating the accuracy of CT planimetry to measure the aortic valve area. The PUBMED and OVID databases were searched up to May 2008. Major criteria for article inclusion was the use of (a) multi-detector computed tomography as a diagnostic test for the assessment of AVA in patients with AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Studies have shown that the valve area is largest during mid-systole 7 with other studies suggesting that the optimal phases correspond to 10%-30% of the R-R interval. [8][9][10] Shah et al 7 concluded that MDCT can provide accurate assessment of aortic valve area compared with TEE and is valuable when the latter is inconclusive.…”
Section: Aortic Stenosismentioning
confidence: 66%
“…Studies have shown that the valve area is largest during mid-systole 7 with other studies suggesting that the optimal phases correspond to 10%-30% of the R-R interval. [8][9][10] Shah et al 7 concluded that MDCT can provide accurate assessment of aortic valve area compared with TEE and is valuable when the latter is inconclusive.…”
Section: Aortic Stenosismentioning
confidence: 66%
“…However, when echocardiography is difficult to perform or is limited in its images, cardiac CT can play a supplementary role in diagnosis. In cases of aortic stenosis, previous studies have shown that the area of the aortic valve opening measured on CT is closely associated with the opening area measured on echocardiography (224, 225, 226). Also, by performing CT, it is possible to accurately diagnose abnormalities such as the bicuspid aortic valve (227, 228).…”
Section: Prefacementioning
confidence: 87%
“…However, it can image the anatomical orifice at sub-0.6 mm resolution with 3D isotropic imaging at any stage of the cardiac cycle to produce an estimate of geometric orifice area. This correlates with but inevitably overestimates EOA calculated echocardiographically 23. In a recent meta-analysis of nine studies involving a total of 437 patients, the mean geometric orifice area measured by MDCT was 1.0±0.1 cm 2 compared with a mean EOA of 0.9±0.1 cm 2 measured by TTE 23…”
Section: Non-echocardiographic Imaging Modalitiesmentioning
confidence: 93%